1995
DOI: 10.1074/jbc.270.38.22608
|View full text |Cite
|
Sign up to set email alerts
|

Heregulin Activation of Extracellular Acidification in Mammary Carcinoma Cells Is Associated with Expression of HER2 and HER3

Abstract: HER2, the erbB-2/neu proto-oncogene product, is a 185-kDa transmembrane glycoprotein related to the epidermal growth factor receptor. Overexpression of HER2 was reported in several human adenocarcinomas, including mammary and ovarian carcinomas. A family of glycoproteins, the heregulin/neu differentiation factors, was characterized and implicated as the ligands for HER2. Recently, it has been shown that HER2 alone is not sufficient to reconstitute high affinity heregulin receptors and that HER3 or HER4 may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
4
25
1
Order By: Relevance
“…The developed RT ± PCR procedure for the detection of c-erbB3 and c-erbB4 mRNA was tested further using a small sub-group of breast tumour samples and was found to be highly reproducible, with a mean densitometry variance of only *4% (not illustrated). Furthermore, analysis of c-erbB3 mRNA expression by RT ± PCR for a series of breast cancer cell lines was in concurrence with the literature, both for those reported as positive (ZR75.1, MCF-7, MDA 453; Lemoine et al, 1992;Kraus et al, 1993;Chan et al, 1995) and negative (MDA 231, A431;Rajkumar and Gullick, 1994) respectively for c-erbB3 mRNA and protein (not illustrated).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The developed RT ± PCR procedure for the detection of c-erbB3 and c-erbB4 mRNA was tested further using a small sub-group of breast tumour samples and was found to be highly reproducible, with a mean densitometry variance of only *4% (not illustrated). Furthermore, analysis of c-erbB3 mRNA expression by RT ± PCR for a series of breast cancer cell lines was in concurrence with the literature, both for those reported as positive (ZR75.1, MCF-7, MDA 453; Lemoine et al, 1992;Kraus et al, 1993;Chan et al, 1995) and negative (MDA 231, A431;Rajkumar and Gullick, 1994) respectively for c-erbB3 mRNA and protein (not illustrated).…”
Section: Resultssupporting
confidence: 84%
“…Con®dence in the optimised RT ± PCR procedure for the detection of c-erbB3 mRNA was initially tested on a series of cell monolayers reported in the literature as positive (ZR75.1, MCF-7, MDA 453; Lemoine et al, 1992;Chan et al, 1995;Rajkumar et al, 1995) or negative (MDA 231, A431; Rajkumar and Gullick, 1994) respectively for c-erbB3 protein or mRNA. Furthermore, assay conditions were carefully optimized by performing simultaneous RT ± PCR of each speci®c primer in combination with aactin on 10 of the breast cancer samples using a range of cycle numbers (20 ± 32) and using conditions identical to those described previously (Knowlden et al, 1997).…”
Section: Simultaneous Pcr Of Er Egfr C-erbb3 and C-erbb4 Cdnamentioning
confidence: 99%
“…In addition to the lack of EGFR expression, HER4 expression was minimally detected. It has been reported that HER2 expression is not detectable by Northern blotting in CHO cells (Chan et al, 1995), but we were able to detect low levels of HER2 expression by both RT-PCR and flow cytometry. HER3 expression in CHO cells was minimally detected by RT-PCR and flow cytometry.…”
Section: Discussioncontrasting
confidence: 51%
“…Our Northern blot analysis (Figure 2) demonstrated that in the adult, two of these ErbB-4-positive tissues, pancreas and muscle, express three molecular weight species of NRG-4. Likewise, multiple mRNA species of NRG-1 and NRG-2 were reported (Chan et al, 1995;Wen et al, 1992). Whether or not the multiplicity of NRG-4 mRNAs is related to the existence of many isoforms of NRG-1 and NRG-2 (Bus®eld et al, 1997;Carraway et al, 1997;Chang et al, 1997;Marchionni et al, 1993;Wen et al, 1994) is currently unknown.…”
Section: Discussionmentioning
confidence: 99%